PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA ARYAWAN PADA PT BANDAR ABADI SHIPYARD - Lia Anggelina; Inggrid Wahyuni Sinaga (Politeknik Negeri Batam, 2017)
PT Bandar Abadi Shipyard is a company engaged in manufacturing and the company is working to improve the quality and quantity of production in the ship building and ship repair. The purpose of this study was to determine the influence of organizational culture variables and work motivation on employee performance at PT. Bandar Abadi Shipyard. The study population was 50 people and the samples used are saturated sampling technique. This study using multiple linear regression data analysis with the help of computer software SPSS version 20.00. Analysis of the data used to test the validity and reliability levels, classical assumptions and hypothesis testing. Results from this study indicate that the organizational culture (X1), and work motivation (X2) positive and significant impact on employee performance (Y) and simultaneously the organizational culture (X1) and work motivation (X2) positive and significant impact on employee performance (Y)